DETERMINATION OF THE ABSOLUTE CONFIGURATION OF NEW PIPERIDIN-4-ONE DERIVATIVE FROM Pellacalyx saccardianus BY NOESY SPECTROSCOPY (Jurnal Teknologi (Sciences & Engineering), 2016)
A new alkaloid, pellacalyxin was isolated from the leaves of Pellacalyx saccardianus of Rhizophoraceae family. Pellacalyxin was analyzed using nuclear Overhauser spectroscopy (NOESY) nuclear magnetic resonance (NMR) technique to determine the absolute configuration. The analysis of absolute configuration of pellacalyxin was supported by X-ray crystallography. 1H-1H NOESY NMR spectroscopy exhibited that pellacalyxin possesses two chiral centers (3S) and (6R).